2018
DOI: 10.30743/mes.v4i1.870
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Peningkatan Kemampuan Koneksi Matematis Siswa Ditinjau Melalui Aplikasi Pendekatan Pembelajaran Savi Berbasis Lingkungan Dan Pembelajaran Ekspositori

Abstract: The purpose of this study was to analyze and describe students' mathematical connection abilities reviewed through the application of SAVI learning approach based on environment and expository learning. This research is a quasi-experimental research, in this study consists of three stages, namely the preparation stage, the implementation phase and the data analysis phase. This study took two parallel classes which were randomly homogeneous by applying different learning methods, namely the experimental and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
68

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 0 publications
1
22
0
68
Order By: Relevance
“…Students will obtain the desired learning experience, which in turn will enhance students' motivation to learn and improve the learning outcomes (Yohani, Rakhmat, & Mulyana, 2014). Several studies have also shown that the application of the SAVI learning model and its modification is effective in supporting the growth of students' mathematical abilities (Pujiastuti, Waluya, & Mulyono, 2018;Siagian & Sembiring, 2018). Besides that, in this teaching material, the mathematical problems given to students are presented in the form of story questions (essays), so that these trains and fosters students' mathematical connection skills.…”
Section: The Results Of Teacher Response Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Students will obtain the desired learning experience, which in turn will enhance students' motivation to learn and improve the learning outcomes (Yohani, Rakhmat, & Mulyana, 2014). Several studies have also shown that the application of the SAVI learning model and its modification is effective in supporting the growth of students' mathematical abilities (Pujiastuti, Waluya, & Mulyono, 2018;Siagian & Sembiring, 2018). Besides that, in this teaching material, the mathematical problems given to students are presented in the form of story questions (essays), so that these trains and fosters students' mathematical connection skills.…”
Section: The Results Of Teacher Response Questionnairementioning
confidence: 99%
“…In this study, the teaching materials were developed based on Somatic, Auditory, Visual and Intellectual (SAVI) approach. Siagian and Sembiring (2018) argued that the SAVI approach enables the learning activities to be more optimal because it involves students' entire senses. Learning using somatic can enrich students' learning experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Kemampuan koneksi matematis merupakan hal yang penting untuk dikuasai oleh siswa (Septian & Rizkiandi, 2017;Siagian & Sembiring, 2018). Hal yang dapat dilakukan untuk bisa menguasai kemampuan koneksi matematis adalah siswa mampu mengaitkan ide matematika dengan pemahaman antar topik dalam matematika.…”
Section: Pendahuluanunclassified
“…Pembelajaran dengan pendekatan SAVI adalah pembelajaran melalui kombinasi pergerakan fisik dan aktifitas intelektual atau berpikir serta melibatkan semua indera yang dalam pembelajaran (Ulvah & Afriansyah, 2016;Siagian & Sembiring, 2018). Pendekatan SAVI memiliki kesesuaian karakter dengan pembelajaran yang ingin mengangkat kemampuan koneksi matematis siswa.…”
Section: Membacaunclassified
“…Matematika merupakan ilmu universal atau bersifat umum dan berlaku bagi seluruh orang pada kehidupan sehari-hari. Matematika yaitu salah satu cabang ilmu pengetahuan dan memegang peranan krusial pada kemajuan IPTEK, oleh karena itu dapat digunakan sebagai alat aplikasi bagi disiplin ilmu lain serta perkembangan matematika itu sendiri (Siagian, 2016). Mengingat pentingnya peran matematika, upaya perbaikan sistem pengajaran matematika selalu menjadi perhatian masyarakat, terutama bagi pemerintah dan pakar pendidikan matematika.…”
unclassified